DISTRIBUIÇÃO E ESTRUTURA DA ASSEMBLÉIA DE PEIXES EM UM RIO SOB INFLUÊNCIA ANTROPOGÊNICA: O CASO DO RIO MEIA PONTE, ALTO DA BACIA DO RIO PARANÁ BRASIL CENTRAL - Oliveira, Monique Pazete de (2008)
The Meia Ponte River basin occupies an area of 12.180 km² of the Goiás State and it is affluent of the right margin of the Paranaíba River, upper Paraná River basin. The water of this basin supplies industrial and production activities with more than 290 enterprises related mainly to industry, mining, cattle raise, agriculture, aquiculture and electric power production. Receives also domestic sewage generated by several urban areas installed along the basin including the city of Goiânia. This study aims to compares the differences among fish assemblages considering the abundance, richness, the Shannon-Wiener diversity Index and constancy; to determine the quality of the aquatic environment taking into account the relation biomass/abundance; and to determine which among hydrological (water velocity, channel width, channel water depth) and physico-chemical variables (luminosity, Secchi water transparency, conductivity, water temperature, turbidity, and dissolved oxygen) determines the fish assemblage structure. Samples of environmental variables and fish were conducted in five stretches (1000 m) located along the main channel of the Meia Ponte River every two month between March 2006 and February 2007, totalizing six collections and embracing the low and high waters seasons. Fish were captured using four set of nets (meshes 12, 15, 20, 25, 30, 35, 50 and 70 mm) and five minnow-traps. It was collected 2.736 individuals distributed in 64 species. Results show that the pattern of the number of constant species along the channel river contrasts with those of the accessory and occasional species. Significant differences among stretches are observed considering the abundance, richness and Shannon-Wiener diversity Index. The analysis cluster indicates that the fish assemblages of the stretches 1, 2 and 3 are different from those downstream the hydroelectric reservoir of Rochedo (stretches 4 and 5). The ABC curves suggests that upperstream stretches (1 to 3) are less polluted that those (4 and 5) downstream the Rochedo reservoir. Two environmental variables structure the fish assemblages the width channel and the water velocity. Anthropogenic impacts influence on the results obtained.